1999
DOI: 10.1021/bi9829130
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-Flow Kinetic Analysis of the Ligand-Induced Coil−Helix Transition in Glutathione S-Transferase A1-1:  Evidence for a Persistent Denatured State

Abstract: Structural studies have suggested that the glutathione S-transferase (GST) A1-1 isozyme contains a dynamic C-terminus which undergoes a ligand-dependent disorder-order transition and sequesters substrates within the active site. Here, the contribution of the C-terminus to the kinetics and thermodynamics of ligand binding and dissociation has been determined. Steady-state turnover rates of the wild type (WT) and a C-terminal truncated (Delta209-222) rGST A1-1 with ethacrynic acid (EA) were measured in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 31 publications
8
66
0
Order By: Relevance
“…The present work shows that this residue is not uniformly important for all substrates : substitution of this tyrosine residue by a phenylalanine residue has a marked effect on the rate of conjugation of the good substrate CDNB, but very little effect on the rate of conjugation of the poor substrate ethacrynic acid. This could be explained if product dissociation were rate-limiting for ethacrynic acid conjugation, as shown very recently for wild-type rat GST A1-1 [36], but not for CDNB conjugation by human GST A1-1 ; the data would require that for ethacrynic acid product dissociation be rate-limiting both in the wild-type enzyme and in the Y9F mutant, where, judging by the results with CDNB, the chemical step appears to be at least 170-fold slower.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The present work shows that this residue is not uniformly important for all substrates : substitution of this tyrosine residue by a phenylalanine residue has a marked effect on the rate of conjugation of the good substrate CDNB, but very little effect on the rate of conjugation of the poor substrate ethacrynic acid. This could be explained if product dissociation were rate-limiting for ethacrynic acid conjugation, as shown very recently for wild-type rat GST A1-1 [36], but not for CDNB conjugation by human GST A1-1 ; the data would require that for ethacrynic acid product dissociation be rate-limiting both in the wild-type enzyme and in the Y9F mutant, where, judging by the results with CDNB, the chemical step appears to be at least 170-fold slower.…”
Section: Discussionmentioning
confidence: 68%
“…There is also evidence that the C-terminal residues (211-222) of the protein, which form a helix in the structure of the SbenzylGSH complex [8], are important for catalysis [20], and they have very recently been shown to determine the dissociation of the GSH-ethacrynic acid conjugate from rat GST A1-1 [36]. From the studies reported here of ligand binding and catalysis by the wild-type and ∆CT enzymes, we come to the following conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction of the rat GSTA1-1 (rGSTA1-1) ⌬209 -222 mutant has been described previously, as have the expression and purification (38,39). Activity of all purified enzymes was determined using the 1-chloro-2,4-dinitrobenzene (CDNB) assay (40).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in the human A1-1 GST (Alpha class), a rapid transition has been proposed involving motions of the flexible C-terminal segment that partially covers the G-site (31). Even the Mu class GST, where the active site is confined by two flexible loops, may display a similar fluctuating accessibility (32).…”
mentioning
confidence: 99%